Chemical modification of chitosan-filled polypropylene (PP) composites: The effect of 3-aminopropyltriethoxysilane on mechanical and thermal properties - Salmah, Husseinsyah, Prof. Madya Dr. Ir.; Faisal, Amri; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Taylor & Francis Group, 2011)
Link to publisher's homepage at http://www.tandfonline.com/